2008
DOI: 10.3998/ark.5550190.0009.815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and study of new antimicrobial benzothiazoles substituted on heterocyclic ring

Abstract: New 2-styryl benzothiazolium salts substituted on the heterocyclic ring have been synthesised by the condensation of 3-alkyl-2-methylbenzothiazolium halides with 4-substituted benzaldehydes. The intramolecular charge transfer from the electron-donor substituent to the benzothiazolium ring is a typical feature of the prepared compounds. This type of benzothiazolium derivatives can be used as pharmaceutical substances as well as compounds with nonlinear optical response. Antimicrobial in vitro activity was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The synthesis of soluble positively charged perylene-based analogs was carried out using a number of biocompatible moieties bearing a positive charge, such as N-methylmorpholinium [ 31 ], O- l -valinyl ester hydrochloride [ 32 ], and benzothiazolium [ 33 ] residues, and introduced them via well-established synthetic procedures ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of soluble positively charged perylene-based analogs was carried out using a number of biocompatible moieties bearing a positive charge, such as N-methylmorpholinium [ 31 ], O- l -valinyl ester hydrochloride [ 32 ], and benzothiazolium [ 33 ] residues, and introduced them via well-established synthetic procedures ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[6] The preparation of benzothiazoles, benzobisthiazoles, and pyridylthiazoles can be a synthetic challenge and various approaches towards their syntheses have been published. [4,7] Begum and Pickup [8] and Cropek et al [9] have shown that transition metal complexes bearing benzothiazole ligands have potential as electrocatalysts for the reduction of carbon dioxide and as photocatalysts for the evolution of hydrogen. Shaaban et al [10] have also successfully applied a benzothiazole ligand system to the Mizoroki-Heck crosscoupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of polyester fibers and their blends, there has been a significant increase in the development of disperse dyes because over 90% of disperse dyes’ usage is for the dyeing of polyester and its blends, and with a significant increase in the world production of polyester fibers compared to other fibers (Aldib and Christie, 2011). Many diazo components have been used in the production of disperse dyes in recent times (Racane et al , 2006; Sigmundová et al , 2008; Towns, 1999; Rangnekar et al , 1999). Disperse dyes based on thiazole, and their dyeing application on polyester fiber and their antimicrobial activity have been reported (Zadafiya et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0369-9420.htm (Aldib and Christie, 2011). Many diazo components have been used in the production of disperse dyes in recent times (Racane et al, 2006;Sigmundov a et al, 2008;Towns, 1999;Rangnekar et al, 1999). Disperse dyes based on thiazole, and their dyeing application on polyester fiber and their antimicrobial activity have been reported (Zadafiya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%